A computational study of the magnetocaloric effect in the LaCr2Si2C compound. (1st June 2020) - Arejdal, M.
Graphical abstract: LaCr2 Si2 C has been studied. Thermal magnetization, susceptibility, specific heat and Binder's fourth-order cumulates of order parameter of the system have been established. The transition temperature has been deduced. Hysteresis loop behaviors have been studied and interpreted. The isothermal magnetic entropy change, adiabatic temperature change and relative cooling power (RCP) for different external magnetic fields are examined. Abstract: We have systematically established and predicted the magnetic behavior and magnetocaloric effect in LaCr2 Si2 C. In the present work, we have employed the Monte Carlo methods in the framework of the (3D) Ising model. Ferromagnetic order of LaCr2 Si2 C is observed below the Curie temperature, which is 18.5 K. From the variation of the magnetism and Binder's fourth-order cumulate of the energy, we deduced that the magnetic phase transition is a second-order (FM) to paramagnetic (PM) transition above Tc. The impacts of both the exchange coupling and the temperature on the hysteresis cycle are treated. Other parameters have also been computed and established as the magnetic entropy change (ΔSM ), which reaches 1.234 J/kg K in a field change of 5 T. The relative cooling power (RCP) attains 13.03 J/kg under an applied field of 5 T.